2003
DOI: 10.1136/jme.29.6.325
|View full text |Cite
|
Sign up to set email alerts
|

Should HIV discordant couples have access to assisted reproductive technologies?

Abstract: In this paper we identify and evaluate arguments for and against offering assisted reproductive technologies (ART), specifically IVF, to HIV discordant couples (male partner HIV positive, female partner HIV negative). The idea of offering ART to HIV discordant couples generates concerns about safety and public health and raises questions such as: what is an acceptable level of risk to offspring and should couples who want this assistance be subject to selection criteria; should they undergo scrutiny about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…With optimal management, the prospect for child rearing appears realistic. Given the recent statements that HIV-1 infection should not serve as a sole contraindication to assisted reproduction, 1,2 in addition to mounting opinion in the field favoring fertility treatment for HIV-1-infected patients, 10,24,25 biases against providing assisted reproduction to HIV-1-seropositive patients appear to be gradually weakening. A permissive attitude toward providing reproductive care to HIV-1-seropositive patients recognizes the autonomy of infected individuals, some of whom would assume risks to attempt to conceive naturally in the absence of reproductive assistance 13 ; additionally, it protects the welfare of the uninfected partner and the offspring, who may be at a higher risk of infection if assisted reproductive services were not available.…”
Section: Discussionmentioning
confidence: 99%
“…With optimal management, the prospect for child rearing appears realistic. Given the recent statements that HIV-1 infection should not serve as a sole contraindication to assisted reproduction, 1,2 in addition to mounting opinion in the field favoring fertility treatment for HIV-1-infected patients, 10,24,25 biases against providing assisted reproduction to HIV-1-seropositive patients appear to be gradually weakening. A permissive attitude toward providing reproductive care to HIV-1-seropositive patients recognizes the autonomy of infected individuals, some of whom would assume risks to attempt to conceive naturally in the absence of reproductive assistance 13 ; additionally, it protects the welfare of the uninfected partner and the offspring, who may be at a higher risk of infection if assisted reproductive services were not available.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Spriggs published a study that identified and evaluated arguments for and against offering ART, specifically IVF, to HIV‐discordant couples (male partner HIV positive, female partner HIV negative) 20…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…In 2003, Spriggs published a study that identified and evaluated arguments for and against offering ART, specifically IVF, to HIV-discordant couples (male partner HIV positive, female partner HIV negative). 20 The idea of offering ART to HIV-discordant couples generates concern about safety and public health and raises questions about the acceptable level of risk to offspring as well as the necessity for couples who want this assistance to be subject to selection criteria (in particular, the question of whether they should undergo exams for their suitability as parents when those who are able to conceive naturally face no such scrutiny and people with other illnesses are given access to ART).…”
Section: Hiv and Ivfmentioning
confidence: 99%
“…The usefulness of the concept of the 'welfare of the child' has been the subject of much debate since the Act (Blyth, 1995;Blyth & Cameron, 1998;Cannold & Gillam, 2002;Devlin & Parkin, 2003;Dower, 2001;Landgridge, 2000;Pennings, 1999;Spriggs & Charles, 2003;Stern, Cramer, Green, Garrod, & De Vries, 2003). In this paper I explore ways in which it might be coherent to talk about the welfare of the child at all in relation to 'potential children' and their implications for practice.…”
mentioning
confidence: 96%